Understanding COVID-19 and its Impact on Social connection at the Outdoor Recreational Spaces Among CQUniversity students - keosilaphone, paniphone (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
Preventive measures have been widely used to stop the COVID-19 outbreak, which may have a devastating impact on the social connection among university students. In particular, the outdoor recreation has been limited due to the COVID-19 restrictions. This study seeks to understand CQUniversity students’ knowledge about COVID-19 preventive measures and identify the consequence of this practice on the social connection at the outdoor recreational spaces by using a mixed-method design (online survey and interview). Central Queensland University Students enrolled in Participatory Health Research completed an online survey (N=22) and participated in an online interview (N=15). The results showed that students understood clearly about COVID-19 preventive measures (N=22, 100%). Students had a high number of social connections at the recreational areas, both in-person (Mean=7, Std=7) and virtually (Mean =2, Std=7) before COVID-19. Conversely, During the COVID-19 outbreak, social contacts at the recreational areas had dropped for in-person (Mean=4, Std=5.5) while connection via online platforms slightly increased (Mean =3, Std=5). Their level of social connectedness during COVID-19 moderately connected (N=8, 36%). Students’ experienced impact on the three levels of socioecological: intrapersonal (e.g. stress, loneliness, and behaviour change), interpersonal (e.g. contacting via social media) and environmental (e.g. parks needed for emotional support).